Effects of vitamin D on steroidogenesis, reactive oxygen species production, and enzymatic antioxidant defense in human granulosa cells of normal and polycystic ovaries. Issue 197 (March 2020) - Masjedi, Fatemeh; Keshtgar, Sara; Zal, Fatemeh; Talaei-Khozani, Tahereh; Sameti, Soodabeh; Fallahi, Sara; Kazeroni, Marjane
Abstract: Polycystic ovary syndrome (PCOS) is accompanied with many disturbances in hormone synthesis and antioxidant defense. Previous reports have indicated that Vitamin D (vit.D) affects gene expression and have roles in normal follicular development. Therefore, we investigated the effects of vit.D on steroidogenesis, apoptosis, reactive oxygen species (ROS) production, and antioxidant defenses of human normal granulosa cells (N-GCs) and granulosa cells from polycystic ovaries (PCO-GCs). Ovarian GCs were obtained during oocyte retrieval procedure from 120 women with PCOS and from 100 healthy women who referred to Shiraz Fertility Center. The isolated GCs were cultured in the presence or absence of vit.D (100 nM), for 48 h. Concentration of sex steroids was measured by ELISA. Glutathione peroxidase (GPx) and superoxide dismutase (SOD) expression and activities were assessed by q-PCR and photometric methods, respectively. The amount of ROS production was estimated using chemiluminescence and fluorescence methods. Cell viability and apoptosis were detected by Annexin-V/propidium iodide detection kit. Basal estrone and progesterone secretion by N-GCs was significantly higher than that of PCO-GCs. Vit.D significantly increased aromatase and 3β-hydroxysteroid dehydrogenase activity in N-GCs and PCO-GCs. Basal expression and activity of GPx, in PCO-GCs were significantly lower than those of N-GCs. Treatment with vit.D significantly increased genes expression and enzyme activities in both groups. Basal ROS in PCO-GCs was markedly greater than that of N-GCs, which was attenuated by vit.D treatment. Cell apoptosis was directly correlated with ROS levels. We conclude that vit.D improved N-GCs and PCO-GCs functions through affecting steroidogenesis and enzymatic antioxidant defense. Under vit.D treatment, PCO-GCs could act more similar to N-GCs.